Microorganism changes in the gut of Apis mellifera surviving for the long term in Camellia oleifera forests - Chen, Longsheng; Li, Zhen; Yuan, Dongju; Chen, Yongzhong; Xu, Yanming; Tang, Wei; Liu, Caixia (Frontiers in Cellular and Infection Microbiology, 2025)
Alpha-galactosides (oligosaccharides) in C. oleifera nectar and pollen cause honey bee larval rot and worker bloats. Honey bee colonies surviving in C. oleifera forests for a long period have low rates of larval rot and worker bloats; however, the mechanism of oligosaccharide metabolism is unclear. In this study, we used metagenomics and metabolomics to investigate the structure and function of the gut flora and the digestion characteristics of oligosaccharides in the gut of A. mellifera foragers (CN group) that had been in the C. oleifera forest for a long period (continuously for 14 years), and those that had not been pollinated with C. oleifera (N group) after 24 h of consumption of C. oleifera honey. The results revealed that the abundance of Gilliamella apicola up to 24.08%, which can metabolize α-galactoside (α-Gal), was significantly higher (P < 0.05) in the gut of foragers in the CN group than in the N group. Additionally, the gut flora of foragers in the CN group carried a significantly higher (P < 0.05) abundance of genes encoding α-galactosidase (Glycoside hydrolase family 4, GH4) than the N group. Similarly, metabolomic results indicated that the three toxic oligosaccharides in C. oleifera honey were lower in the gut of CN group foragers. These results suggest that the gut flora of A. mellifera, which inhabits oil tea forests for long periods of time, changes and adapts to the predominant ecological niche, enhancing the host’s ability to metabolize toxic oligosaccharides. This important discovery provides positive guidance for the subsequent directions for breeding of A. mellifera (G. apicola enrichment and GH4 upregulation), specialized in pollinating C. oleifera.